Association between mild cognitive impairment and dementia and undernutrition among elderly people in Central Africa: some results from the EPIDEMCA (Epidemiology of Dementia in Central Africa) programme. Issue 2 (23rd June 2015) - Pilleron, Sophie; Jésus, Pierre; Desport, Jean-Claude; Mbelesso, Pascal; Ndamba-Bandzouzi, Bébène; Clément, Jean-Pierre; Dartigues, Jean-François; Preux, Pierre-Marie; Guerchet, Maëlenn; ,
Abstract : Several studies in Western countries have shown an association between cognitive disorders and low BMI or weight loss in elderly people. However, few data are available in Africa. We analysed the association between cognitive disorders and undernutrition among elderly people in Central Africa. A cross-sectional, multicentre, population-based study using a two-phase design was carried out in subjects aged 65 years and above in the Central African Republic (CAR) and the Republic of Congo (ROC). All subjects were interviewed using the Community Screening Interview for Dementia, and those with low performance were clinically assessed by a neurologist and underwent further psychometrical tests. Diagnostic and Statistical Manual-IV and Petersen's criteria were required for the diagnoses of dementia and mild cognitive impairment (MCI), respectively. Undernutrition was evaluated using mid-upper arm circumference (MUAC) < 24 cm, BMI < 18·5 kg/m 2 and arm muscular circumference (AMC) < 5th percentile. Multivariate binary logistic regression models were used to estimate the associations. In CAR, MCI was associated with MUAC < 24 cm (OR 0·7, 95 % CI 0·4, 1·0) and dementia with BMI < 18·5 kg/m 2 (OR 2·3, 95 % CI 1·6, 3·1), AMC < 5th percentile (OR 2·3, 95 % CI 1·1, 4·6) and MUAC < 24 cm (OR 1·8, 95 % CI 1·4, 2·4). In ROC, both MCI and dementia were associated with all markers of undernutrition, but only AMC < 5th percentile was significantly associated with MCI (OR 3·1, 95 % CI 1·9, 4·8). In conclusion, cognitive disorders were associated with undernutrition. However, further studies are needed to elucidate the relationship between MCI and undernutrition in CAR.